Volatility of interest rates in the euro area: evidence from high frequency data - Nuno Cassola; Claudio Morana (European Central Bank (ECB), 2003)
This paper estimate the factors underlying the volatility of the euro overnight interest rate and its transmission along the euro area money market yield curve. A new multivariate unobserved components model is proposed allowing for both long-memory and stationary cyclical dynamics. Using hourly data the estimates show repetitive intradaily and monthly patterns that can be explained by the microstructure of the money market and the institutional features of the Eurosystem's operational framework for monetary policy implementation. Strong persistence is dedected in all log-volatility processes and two common long-memory factors are extracted. The first factor explains the long-memory dynamics of the shortest maturity. The second factor explains the transmission of volatility along the money market yield curve. We find evidence that most liquidity effects are cyclical, confined to the ned of reserve maintenance periods, and are not transmitted along the money market yield curve.
Keywords: C32; E43; F30; G10; 330; fractional integration and cointegration; liquidity effect; money market interest rates; Money market microstructure; stochastic volatility